The March of the White Elephants - Tanner, Craig (South Africa, 2015)
The film reveals the real legacy of the FIFA World Cup - state of the art stadiums that were built to stage a four-week tournament will stand idle, soaking up funds needed for basic services and for health, housing and education. The filmmakers visit the sites of the last two World Cups, Brazil & South Africa, to get testimony from social activists who make it clear that FIFA is a modern day parasite abusing countries for the love of Football.
Verzio Film Festival Submission
Keywords: Documentary films